Assessment of dosimetric parameters in mammography employing a homemade ionization chamber - Silva, Jonas Oliveira da; Caldas, Linda V. E. (Scientia Plena, 2016)
X-ray mammography examination is the reference tool to discover breast cancer in an early stage. The mammography unit must follow an accurate quality control program that covers both patient and staff radiation protection. Plane parallel ionization chambers are the reference instrument for dosimetry in mammography beams, but they can represent higher cost for small clinics in countries as Brazil. In this work, it is presented a low cost ionization chamber for mammography X-rays energy range dosimetry developed at IPEN.  The homemade ionization chamber has a sensitive volume of 6.0 cm3 and it was utilized to execute quality control tests in two distinct mammography systems: a GE Senographe DMR-plus and a Philips VMI Graph Mammo. The setups for the tests performed agreed with the IAEA HHS 2 and 17 recommendations. A breast phantom of various PMMA thicknesses was utilized in this work. The homemade ionization chamber performance was compared to that of a commercial one. The maximum difference between the incident air kerma measured with the reference ionization chamber and the developed one was only 5.62% for the GE equipment and only 4.42% for the Philips equipment. The homemade ionization chamber presented an excellent performance in incident air kerma and HVL measurements for the radiographic techniques utilized in the present work. All the results obtained were within IAEA specifications.